If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(2x-3)+15=0
We multiply parentheses
-6x+9+15=0
We add all the numbers together, and all the variables
-6x+24=0
We move all terms containing x to the left, all other terms to the right
-6x=-24
x=-24/-6
x=+4
| -5/2=3/4+n | | 17.20=3g+3.58 | | X+6=-7x-10 | | -4(5n+6)+2(8n+8)=4 | | -5/2=3/4=n | | 14=8x2 | | 10p–3p=7p | | -20=v/4-8 | | v/15=6/5 | | r+11=18 | | 2(2x-4)+6=5x-10 | | 3p+2=6p-10 | | -11-9x=16-10x | | |5x-6|=12 | | -5(q+3/5)=-4 | | 4+x+7x=60 | | X/160=4.5-x/30 | | 273=188-v | | 6^2x+1=17 | | -11-9x=16-10× | | 1.5(30-n)=4 | | 68.00+x=75.83 | | -1=4+3x | | 68.00+x=$75.83 | | -6u+24=(u-4) | | (5(x+3)+(6x-1)+(2x+4)=96 | | x+81=222 | | 1/5x-6=-4/5x+5 | | 5x+4+3x=100 | | 3(u+3)=-5u-31 | | -6(y+7)=7-5y | | 3t-4=t-2 |